1977
DOI: 10.1002/apmc.1977.050620107
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of vinyl ketones in free radical copolymerization with methyl methacrylate and vinyl acetate

Abstract: Die Ange~:andte Mak~-oniolekulare Chemie 62 ( I 977) 85-90 ( NI-. 891 ) SUMMARY:The reactivity of some monomer vinyl ketones in the radical copolymerization with methyl methacrylate and vinyl acetate was studied on the basis of the Taft equation. It was concluded that the relative reactivities of the vinyl ketones in radical reactions increase with increasing electron-withdrawing nature of the vinyl ketone substituent. Polar and steric effects d o not affect the reactivity. ZUSAMMENFASSUNG:Die Reaktivitat vers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1978
1978
2006
2006

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…It has also been reported that copolymerization greatly effects the glass‐transition temperature of the polymers 10. Moreover, while methyl methacrylate has been reported to be more reactive towards vinyl ketones,11 the thermal stability of poly(vinyl acetate) has been reported to be more. Also, the T g of poly(vinyl acetate) is comparable to poly(methyl methacrylate).…”
Section: Introductionmentioning
confidence: 99%
“…It has also been reported that copolymerization greatly effects the glass‐transition temperature of the polymers 10. Moreover, while methyl methacrylate has been reported to be more reactive towards vinyl ketones,11 the thermal stability of poly(vinyl acetate) has been reported to be more. Also, the T g of poly(vinyl acetate) is comparable to poly(methyl methacrylate).…”
Section: Introductionmentioning
confidence: 99%